The Influence of Education, Length of Service and Workload on Employee Performance at the Serang District Health Office - Acih Acih; Siti Oni Isnenti; Ahmad Enuh; Abdurrohman Abdurrohman; Surya Alam (Institute of Computer Science (IOCS), 2026)
This study investigated how education level, length of service, and workload affect employee performance at the Serang Regency Health Office. Employing a quantitative descriptive–causal approach, the research used a census method involving all 92 civil servants to ensure full population representation. Data collection relied mainly on structured questionnaires with a five-point Likert scale, supported by interviews, direct observations, and document review. The data were analyzed using descriptive statistics and multiple linear regression with SPSS software, following validity, reliability, and classical assumption testing to ensure the suitability of the regression model. The results demonstrate that education level and length of service have positive and statistically significant effects on employee performance, indicating that higher educational attainment and longer work experience contribute to better performance outcomes. In contrast, workload shows a significant negative effect, suggesting that excessive or poorly managed workloads hinder effectiveness and productivity. Simultaneously, all three variables significantly influence performance, with the model explaining 62.7% of performance variance. Education emerged as the most influential positive factor, while workload was the strongest negative determinant, emphasizing the importance of integrated human resource policies that balance capability development and workload management